Effects of Pioglitazone on Insulin Sensitivity and Serum Lipids in Obese Cats. (25th November 2013) - Clark, M.; Thomaseth, K.; Dirikolu, L.; Ferguson, D. C.; Hoenig, M.
<x xml:space="preserve">Abstract</x> Background Pioglitazone is a thiazolidinedione (TZD) insulin sensitizer approved for use in human type 2 diabetes mellitus. Therapeutic options for diabetes in cats are limited. Objective To evaluate the effects of pioglitazone in obese cats, which are predisposed to insulin resistance, to assess its potential for future use in feline diabetes mellitus. Animals A total of 12 obese purpose‐bred research cats (6 neutered males and 6 spayed females, 5–7 years of age, weighing 5.4–9.8 kg). Methods Randomized, placebo‐controlled 3‐way crossover study. Oral placebo or pioglitazone (Actos™; 1 or 3 mg/kg) was administered daily for 7‐week periods, with IV glucose tolerance testing before and after each period. Results Three mg/kg pioglitazone significantly improved insulin sensitivity (geometric mean [95% CI] 0.90 [0.64–1.28] to 2.03 [1.49–2.78] min −1pmol−1L; P = .0014 versus change with placebo), reduced insulin area under the curve during IVGTT (geometric mean [range] 27 [9–64] to 18 [6–54] min∙nmol/L; P = .0031 versus change with placebo), and lowered serum triglyceride (geometric mean [range] 71 [29–271] to 48 [27–75] mg/dL; P = .047 versus change with placebo) and cholesterol (geometric mean [range] 187 [133–294] to 162 [107–249] mg/dL; P = .0042 versus change with placebo) concentrations in the obese cats. No adverse effects attributable to pioglitazone were evident in the otherwise healthy obese cats at this dosage and duration. Conclusions and Clinical Importance Results of this study support a positive effect of pioglitazone on insulin sensitivity and lipid metabolism in obese cats, and suggest that further evaluation of the drug in cats with diabetes mellitus or other metabolic disorders might be warranted.